Project Caring for Carers: An Experience Report - Marques Muniz, Sâmila; Piller Albino Marques, Nadine; Afonso Pereira, Isabela; Rodrigues de Faria, Eliane; Reis Rente, Maria Carolina; de Carvalho Neves, Laise; Azarias de Paiva, Glauciana (Guará Journal, 2019)
The  precepts  of  a  healthy  diet  are  essential  to  large demands  of  nutritional  pregnancy  and  events  related to  it,  such  as  lactation.  Thus,  it  is  clear  that  the empowerment  of  women  on  a  balanced  diet  rich  in nutrients  is  necessary,  since  nutrition  is  one  of  the most  important  pillars  for  the  health  of  the  mother-child  binomial.  Thus  the  objective  of  this  study  was  to carry  out  educational  strategies  with  participants  from the  pregnant  and  expectant  mothers  group  in the waiting room, aiming at promoting health and training about the nutritional needs peculiar to gestation and lactation.
Keywords: Healthy diet; Pregnancy; Nutritional intervention; Pregnancy supply; Recommended dietary allowances